Size Matters: Cigarette Size and Quitting Behaviour Among Male Smokers in An Urban Slum Of West Bengal - Shahbabu, Bhaskar; Sarkar, Ishita; Basu, Rivu (Indian Journal of Community Health, 2024)
Introduction: Tobacco kills half of its users and globally every year around 8 million deaths are attributable to tobacco use. All forms of tobacco are harmful and there is no safe level of exposure to tobacco but cigarette smoking is the most common and notorious since it kills not only its users but also the innocent passive bystanders. Objectives: The study was conducted to determine the prevalence of cigarette use, minimum length of cigarette (nicotine portion) to quench the craving, level of nicotine dependence along with their stage of change (in behaviour to quit tobacco use) and also to find out its determinants among males above 15 years residing in the urban field practicing area of a Public Health Institute. Materials and methods: A community based observational, cross-sectional study was conducted in a slum of West Bengal. Data was collected as per a pre-designed and pre-tested schedule adapted from GATS India Questionnaire. Males above 15 years of age residing in the study area were interviewed during house-to-house visit. Results: A total of 352 study participants were interviewed. 38.4% of study participants consumes cigarettes on a regular basis. Study participants with a positive family history of tobacco use are 2.1 times (95% CI: 1.3, 3.4) more probable to use cigarettes. Half of the population are in stage of precontemplation and 43.7% of them are having high level of nicotine dependency. 66.7% of them do not need to consume the full length of a cigarette to quench their craving. Those with younger age of initiation (OR 5.35 95%CI:2.5,11.2) and consume full length of cigarette (OR 2.72, 95% CI: 1.3,5.7) are having more probability of high nicotine dependency than their counterparts. Odds of willingness to quit is significantly more among those who don’t require full length of a cigarette even when adjusted with various covariates found significant in univariate regression. Conclusion: Length of the cigarettes (nicotine portion) may be reduced to at least half the size of present standard length to not only decrease the nicotine dependence but also to encourage quitting behaviour among the users.